Impact of serum carotenoids on cardiovascular mortality risk in middle-aged and elderly adults with metabolic syndrome - Han, Jing; Wang, Ruiyun; Bai, Lijuan; Liu, Yun; Liao, Man; Zhang, Liting; Liu, Lihua; Qi, Benling (Frontiers in Nutrition, 2024)
Metabolic syndrome (MetS), characterized by abdominal adiposity, hypertension, hyperglycemia, and dyslipidemia, is associated with dysregulated immune function, elevated oxidative stress, and chronic low-grade inflammation. Aging exacerbates insulin resistance and the prevalence of MetS. Dietary antioxidants, such as carotenoids, may play a role in preventing cardiovascular disease (CVD) mortality, but evidence remains mixed, particularly among middle-aged and elderly individuals with MetS.We analyzed data from 6,601 participants aged 40 years and above with MetS from the National Health and Nutrition Examination Survey (NHANES) III (1988III ( -1994) ) and NHANES 2001-2006 cycles. Serum concentrations of α-carotene, β-carotene, lycopene, β-cryptoxanthin, and combined lutein/zeaxanthin were quantified.Participants were followed for a median of 16.8 years. Cox proportional-hazards models were used to assess the association between serum carotenoid concentrations and CVD mortality risk, with adjustment for potential confounders.During the follow-up period, 1,237 CVD deaths were identified. Analysis revealed an inverse dose-response relationship between serum lycopene levels and cardiovascular mortality risk. Compared to the lowest quartile, the multivariable-adjusted hazard ratios (95% confidence intervals) for ascending quartiles of serum lycopene were 0.84 (0.71, 1.00), 0.87 (0.74, 1.03), and 0.77 (0.61, 0.97), with a significant trend (P = 0.039). No significant associations were observed for other carotenoids.In this prospective cohort study of 40-year-old and older individuals with MetS, we observed an inverse association between serum lycopene levels and CVD mortality risk.